An EOQ model for non-instantaneous deteriorating items with ramp-type demand in a two-warehouse facility. (26th August 2021) - Hasan, Ahmad; Kausar, Amrina; Verma, Mona
The present study develops an EOQ model for non-instantaneous deteriorating items, having ramp-type demand in a two-storage facility under partially backlogged shortages. Here, it is supposed that the items are non-instantaneously deteriorating in nature, i.e., the deterioration in them does not start immediately but starts after a time lag. Moreover, demand rate is supposed to be increasing initially and stable thereafter. This type of demand pattern is known as 'ramp-type demand'. The aim of the model is to minimise the total cost by jointly optimising the cycle length and time at which the rented warehouse gets exhausted. The numerical analysis and sensitivity analysis is carried to demonstrate the model characteristics.